2011
DOI: 10.1021/cg200410b
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Four Stereoisomers of the Heme Fe–O Cyclic Dimer in the Crystalline Phase Behavior of Synthetic Hemozoin: Relevance to Native Hemozoin Crystallization

Abstract: Hemozoin is a crystalline byproduct formed upon host hemoglobin digestion in malaria-infected blood cells, crucial for parasitic survival. On the basis of published spectroscopic and X-ray powder diffraction (XRPD) data, hemozoin is believed to be very similar to the synthetic compound β-hematin, which consists of cyclic centrosymmetric dimers of ferriprotoporphyrin IX [Fe(3+) PPIX] molecules coordinated via Fe–O bonds. The enantio-facial symmetry of Fe(3+) PPIX implies, however, that four different Fe–O cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
79
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(87 citation statements)
references
References 33 publications
8
79
0
Order By: Relevance
“…The H-bonds in the minor phase unit cell are somewhat shorter than in the major phase unit cell. These results are in excellent agreement with the predominant hydrogen bond length of 2.65 Å, obtained from an analysis of about 5000 species extracted from the Cambridge Database 18 On the basis of the results of our calculations regarding the energetics of the different stereoisomers of the Fe(3+) PPIX dimer, we suggest that β-hematin nucleation begins with dimerization via the formation of ironÀcarboxylate bonds between two Fe(3+) PPIX monomers. At this stage, the most stable cd1 1 stereoisomer forms predominantly, but because the three isomers are close in energy, the cd1 2 and cd2 stereoisomers may also form in smaller quantities.…”
Section: ' Materials and Methodssupporting
confidence: 87%
See 4 more Smart Citations
“…The H-bonds in the minor phase unit cell are somewhat shorter than in the major phase unit cell. These results are in excellent agreement with the predominant hydrogen bond length of 2.65 Å, obtained from an analysis of about 5000 species extracted from the Cambridge Database 18 On the basis of the results of our calculations regarding the energetics of the different stereoisomers of the Fe(3+) PPIX dimer, we suggest that β-hematin nucleation begins with dimerization via the formation of ironÀcarboxylate bonds between two Fe(3+) PPIX monomers. At this stage, the most stable cd1 1 stereoisomer forms predominantly, but because the three isomers are close in energy, the cd1 2 and cd2 stereoisomers may also form in smaller quantities.…”
Section: ' Materials and Methodssupporting
confidence: 87%
“…This is reflected in the deviation from planarity. In this respect, the geometry of the dimers in the crystal is in better agreement with the refinement of Straasø et al, 18 where the structure of the monomer is based on that of a recently reported complex of Fe(3+) PPIX with halofantrine, 75 as compared to the refinement of Pagola et al, 6 where the structure of the monomer is based on that of R-chlorohemin. 20 The optimized OH 3 3 3 O distances (in the H-bonds between adjacent dimers) range from 2.62 to 2.68 Å with some variation between the different stereoisomers and the different spin states.…”
Section: ' Materials and Methodssupporting
confidence: 81%
See 3 more Smart Citations